Efficacy and safety of Abelmoschus moschatus capsules combined with tripterygium glycoside tablets on diabetic nephropathy: A systematic review and meta-analysis - Zhou, Peipei; Hao, Zhenning; Xu, Weilong; Zhou, Xiqiao; Yu, Jiangyi (Frontiers in Pharmacology, 2022)
Background: Diabetic nephropathy (DN) is one of the most serious chronic micro-vascular complications of diabetes and the leading cause of end stage kidney disease (ESRD) worldwide, with reduced expectancy and quality of life and colossal financial and social burden worldwide. In spite of emerging treatments on DN, effective therapy on delaying the progression of DN is still lacking. In clinical practice, there are many studies focusing on Abelmoschus Moschatus capsule (AM) together with Tripterygium Glycosides tablets (TG) in the treatment of DN and excellent results have been obtained. Objective: To evaluate the efficacy and safety of AM combined with TG in the treatment of DN. Methods: Databases including Pubmed, Web of Science, Cochrane Library, Embase, CNKI, WF and VIP were searched from their inception to March 1,2022. The “risk of bias” evaluation tool produced by Cochrane Collaboration Handbook was used for evaluating the quality of the included studies. Revman 5.3 software was used for meta-analysis. Results: 11 studies with a total of 1072 participants were included for this meta-analysis. Our results showed that AM combined with TG plus basic treatment could lower levels of 24h-UP [MD=-0.18; 95%CI: (-0.21, -0.14); p<0.00001], Scr [MD=-15.29; 95%CI: (-28.69, -1.88); p=0.03], and BUN [MD=-1.18; 95%CI:(-1.69, -0.68); p<0.00001]. Meanwhile, adverse reaction rate increased in combination group[RR=1.88; 95%CI:(1.26, 2.82); p=0.002]. Conclusion: Current evidence suggests that AM combined with TG may be more effective in the treatment of DN, which will be highly beneficial to further theoretical discussion and practical clinical applications. However, the safety can’t be ignored because of nearly increasing 2-fold adverse events though they can be mitigated through systematic treatment. Meanwhile, due to low quality of the included studies, great possibility of publication bias and large heterogeneity among different studies, the results of our review should be evaluated with more prudence and high-quality RCTs are warranted to confirm this in the future.